The Transcultural Dynamics of Naming: The Appropriation and Contestation of Evangelical and Pentecostal as Identity Markers in Local Contexts. (17th April 2019) - Rakow, Katja; Berg-Chan, Esther
Abstract : In our afterword to the special issue on the negotiation of Christian identities between global entanglement and local identity politics, we shed light on what unites the four contributions and provide some questions that invite us to think further. We argue that all four of the presented case studies demonstrate that naming is a dynamic, contested and on-going process that unfolds between the local and the global and to which we thus refer to as the "transcultural dynamics of naming". We ask if these dynamics play out differently in everyday life practices and institutional politics; if these dynamics have to be analysed as instances of identity politics or if other concepts might offer more analytical purchase; and finally, we ask how religious identifications materialize on the ground and what material effects they might produce.